EKSISTENSI BITCOIN OLEH SATOSHI NAKAMOTO TERHADAP KEBIJAKAN MONETER CHINA - E, Fatjri Kurniawan; Retnaningsih, Umi O. (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
Prior to the growth of digitalization globally, the value of bitcoin was less fascinated and unpopular. In the first of bitcoin trials, it was use by a person in America who went to Papa’s John Pizza and he used more than a thousand coins to purchase a slice of it. But nowadays, bitcoin knowns as the most luxurious things in the world. The bitcoin appearances had caught many attentions, including China government. This research would explained how bitcoin existence could impact monetary policy in China.Discussion arranged with neo-liberalism perspective and social networking theory, together with qualitative methodology and data collection method such as observation, documents and reports. The researcher also used analysis from different sources including books, journal, website, newspaper and mass media. The states actor played important role toward this research.The results showed the China’s detention through their policy to bitcoin existence by closed the exchange building, realization of the Yuan digital project, and increased cooperation between the government and local company toward digital money. The government’s strategy seems effective to detained bitcoin movement. This plans also reduction the Chinese intensity to deal with bitcoin. Also, the Chinese government endeavour towards digital yuan development aims to improve their monetary stabilization and achieve the national goals.  Keyword: Bitcoin, Satoshi Nakamoto, Digital Money, China Government, Monetary Policy.